2018
DOI: 10.1111/dme.13847
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre, UK, retrospective, observational study to assess the effectiveness of insulin glargine 300 units/ml in treating people with Type 1 diabetes mellitus in routine clinical practice (SPARTA)

Abstract: Aim To conduct an open‐label study to provide UK real‐world evidence regarding the use of insulin glargine 300 units/ml (U300) in people with Type 1 diabetes mellitus. Methods People with Type 1 diabetes who had been prescribed U300 ≥6 months before data collection and had HbA1c levels recorded within 3 months prior to U300 (baseline) were included. The primary endpoint was change in HbA1c from baseline to month 6 after U300 initiation. Other endpoints included number of documented hypoglycaemic and diabetic k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 10 publications
4
14
1
Order By: Relevance
“…The 6-month extension of the EDITION 4 trial found comparable glucose control in both treatment groups and similar rates of hypoglycemic events with Gla-100 and Gla-300 [49]. These findings are corroborated by a real-world, observational, retrospective study of patients in the UK which reported that there was no major change in the risk of severe hypoglycemia (1 vs. 2%) with initiation of Gla-300 after 6 months despite a significant decrease in HbA1c of 0.4% (4 mmol/mol) and there was no significant weight gain [50].…”
Section: Gla-300 Versus Gla-100supporting
confidence: 55%
“…The 6-month extension of the EDITION 4 trial found comparable glucose control in both treatment groups and similar rates of hypoglycemic events with Gla-100 and Gla-300 [49]. These findings are corroborated by a real-world, observational, retrospective study of patients in the UK which reported that there was no major change in the risk of severe hypoglycemia (1 vs. 2%) with initiation of Gla-300 after 6 months despite a significant decrease in HbA1c of 0.4% (4 mmol/mol) and there was no significant weight gain [50].…”
Section: Gla-300 Versus Gla-100supporting
confidence: 55%
“…Similar findings were reported in retrospective observational studies such as SPARTA in the UK [14] and REALITY in Canada [18]. In the SPARTA study, the researchers investigated 300 T1DM patients who were switched to Gla-300.…”
Section: Discussionsupporting
confidence: 61%
“…Although real-world data on the use of Gla-300 in T1DM are limited, the SPARTA trial, a retrospective, observational study in the UK, recently demonstrated that Gla-300 administered to patients with T1DM was associated with a significant reduction in HbA1c and no increase in hypoglycemia [14]. The issue of an unacceptably low insulin titration was also revealed in the trial.…”
Section: Introductionmentioning
confidence: 99%
“…In one retrospective study, the number of nocturnal hypoglycaemic events was significantly reduced within 2 weeks after patients with T1DM were switched from Gla‐100 to Gla‐300 14 . In the SPARTA study, the incidence of SH remained similar before and 6 months after initiation of Gla‐300, despite a significant HbA1c reduction of 0.4% 15 …”
Section: Discussionmentioning
confidence: 99%
“…14 In the SPARTA study, the incidence of SH remained similar before and 6 months after initiation of Gla-300, despite a significant HbA1c reduction of 0.4%. 15 This post hoc, exploratory analysis has some limitations.…”
Section: Discussionmentioning
confidence: 99%